การจัดการความรู้และพัฒนาชุดความรู้ทางวิทยาศาสตร์ จากภูมิปัญญาท้องถิ่น เตาถลุงสินแร่เหล็กน้ำพี้ ตำบลน้ำพี้ อำเภอทองแสนขัน จังหวัดอุตรดิตถ์ - นะเที่ยง, ไพโรจน์; เกษวิริยะกิจ, ชัชพล; หรรษนันท์, สุรพงษ์ (วารสารวิชาการเทคโนโลยีอุตสาหกรรมและวิศวกรรม มหาวิทยาลัยราชภัฏพิบูลสงคราม, 2019)
This study is focused on knowledge management and development of scientific knowledge from local wisdom on Namphi iron-smelting furnaces in Namphi sub-district, Thong Saen Khan district, Uttaradit province. The study found that the ancient Namphi iron smelting process was a direct iron-smelting process. The figure of the ancient Namphi iron-smelting furnaces was domed. By applying the direct iron-smelting process, smelting Namphi iron weighed 5, 15, and 30 kilograms could obtain steel weighed 0.95, 3.16, and 4.33 kilograms, respectively. The result of developing the furnace efficiency for Namphi iron-smelting by using a cupola furnace showed that smelting Namphi iron weighed 5 kilograms could obtain steel weighed 1.4 kilograms, and the average smelting time was 1.06 hours.